2014
DOI: 10.1515/jpem-2013-0157
|View full text |Cite
|
Sign up to set email alerts
|

The effect of childhood obesity on cardiac functions

Abstract: Obesity is a metabolic disorder defined as excessive accumulation of body fat, which is made up of genetic, environmental, and hormonal factors and has various social, psychological, and medical complications. Childhood obesity is a major indicator of adult obesity. The aim of this study is to evaluate the cardiac functions via electrocardiography (ECG), echocardiography (ECHO), and treadmill test in childhood obesity. A patient group consisting of 30 obese children and a control group consisting of 30 non-obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As a result, the autonomic disparity noticed in obese subjects may have an effect on intra-atrial and inter-atrial conduction times, and leave them prone to develop atrial arrhythmias such as atrial fibrillation [19]. Uner et al reported that PWD was significantly higher in obese patients [37]. Similarly, in this study, we found that Pmax, Pmin and PWD were significantly higher in obese patients and there was an important correlation between inter-atrial and intra-atrial EMD and PWD.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the autonomic disparity noticed in obese subjects may have an effect on intra-atrial and inter-atrial conduction times, and leave them prone to develop atrial arrhythmias such as atrial fibrillation [19]. Uner et al reported that PWD was significantly higher in obese patients [37]. Similarly, in this study, we found that Pmax, Pmin and PWD were significantly higher in obese patients and there was an important correlation between inter-atrial and intra-atrial EMD and PWD.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the results of the present study indicate that early overnutrition in rats is associated with decreased insulin sensitivity in the short-term, both in the heart and in the aorta. This suggests that in a context of increased nutrients and energy supply, alterations of insulin signaling in the vasculature and heart arise early, possibly explaining the finding of heart dysfunction in obese children [53][54][55][56] and highlighting the importance of an early intervention.…”
Section: Discussionmentioning
confidence: 92%
“…With regard to our case, in the patient´s medical history we found he suffered from obesity (BMI > 95 th percentile), being classified as ASA-I when perhaps should have been scored as ASA-II. Obesity may be associated to increased heart rate, hypertension and left ventricular hypertrophy, all of which may lead to ventricular ectopy and tachycardia [20,21]; however, postoperative echocardiogram revealed normal left ventricular dimension or wall thickness. We also found that the child lost his mother-due to cancer-few months before the surgery.…”
Section: Discussionmentioning
confidence: 99%